Dimensions of Basra Gulf Cup Football Championship in Iraqi Daily Newspapers Articles: An Analytical Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Since its inception in 1970, the Gulf Cup football championships have not received as much attention as the 25th Gulf Cup in 2023, hosted by the Iraqi city of Basra. This edition garnered significant interest across various political, athletic, social, and other dimensions. Gulf and Iraqi media devoted extensive coverage to this sporting event, including Iraqi sports journalism in all its forms, with a notable emphasis on the journalistic art of opinion articles in its various types.The significance of this research lies in highlighting the dimensions covered by opinion articles in Iraqi daily newspapers regarding the Gulf Cup in Basra. The researcher selected four daily newspapers for this study, as they consistently covered the tournament, publishing articles and columns across different sections, not limited to sports pages.The research concluded with several findings, most notably that the opinion articles in Iraqi daily newspapers predominantly focused on political dimensions, emphasizing a significant rapprochement between Iraq and its Gulf neighbors. Additionally, the social dimension was highlighted, showcasing the renowned Iraqi hospitality, with locals opening their homes and extending generous hospitality to visitors. The organizational, competitive, and media dimensions were also prominent. The results indicated that the "opinion columns" ranked highest among other types of articles published across various newspaper sections.